2012
DOI: 10.1143/jpsjs.81sa.sa013
|View full text |Cite
|
Sign up to set email alerts
|

Flow-History-Dependent Behavior of Entangled Polymer Melt Flow Analyzed by Multiscale Simulation

Abstract: Polymer melts exhibit flow-history-dependent behavior. To clearly show this behavior, we have investigated the flow behavior of an entangled polymer melt around two cylinders placed in tandem along the flow direction in a two-dimensional periodic system. In this system, polymer states around a cylinder on the downstream side differ from those around a cylinder on the upstream side because the former have a memory of the strain they experienced when passing around the cylinder on the upstream side but the latte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…By comparing the velocity and cross section area profiles with the end-point distribution for the dumbbell connective vectors, for dumbbells located in Lagrangian particles along typical places along the spinning line, we show that our multiscale simulation method successfully bridges the microscopic state of the system with its simultaneous macroscopic flow behavior. It is also confirmed that the present schemes gives good agreements two parallel plates 33,35,36,[41][42][43][44][45][46][47]50) , flows around an infinitely long cylinder 37,40,48,49) , flows in between eccentric rotating cylinders 38,39) and so forth. As far as we know, no one has ever 28,29) or NAPLES 26) , among many others.…”
Section: Department Of Chemical Engineering Kyoto University Kyoto supporting
confidence: 77%
See 1 more Smart Citation
“…By comparing the velocity and cross section area profiles with the end-point distribution for the dumbbell connective vectors, for dumbbells located in Lagrangian particles along typical places along the spinning line, we show that our multiscale simulation method successfully bridges the microscopic state of the system with its simultaneous macroscopic flow behavior. It is also confirmed that the present schemes gives good agreements two parallel plates 33,35,36,[41][42][43][44][45][46][47]50) , flows around an infinitely long cylinder 37,40,48,49) , flows in between eccentric rotating cylinders 38,39) and so forth. As far as we know, no one has ever 28,29) or NAPLES 26) , among many others.…”
Section: Department Of Chemical Engineering Kyoto University Kyoto supporting
confidence: 77%
“…So far, for flow problems of polymeric fluids a limited number of this type of multiscale simulations have been performed. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Actually, the MSS method has…”
Section: -3)mentioning
confidence: 99%
“…However, the extension to the two-and three-dimensional cases is also possible by incorporating the algorithms developed in, for example, Refs. [16][17][18][19]. Second, almost perfect parallelization efficiency (i.e., using N CPUs in the parallel computation speeds up the calculation compared to using a single CPU by N times) is achieved in a parallel computation with as many CPUs as there are MD cells by assigning each CPU to an MD cell [21].…”
Section: Discussionmentioning
confidence: 99%
“…De et al proposed the scale-bridging method, which can correctly reproduce the memory effect of a polymeric liquid, and demonstrated the nonlinear viscoelastic behavior of a polymeric liquid in slab and cylindrical geometries [14,15]. The multiscale simulation for polymeric flows with the advection of memory in two and three dimensions was developed by Murashima and Taniguchi [16][17][18]. We have also developed a multiscale simulation of MD and computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…6 (a) and (b). [142][143][144] Using this MSS method, both macroscopic ( Fig. 6 (c-i)) and microscopic ( Fig.…”
Section: Mss Methods Using Coarse-grained Modelsmentioning
confidence: 99%